PROBLEMS OF TRANSLATING GENDER TERMS IN ENGLISH AND UZBEK - Omonov, Baxtiyorjon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This article provides a comprehensive analysis of the typological, lexical-semantic, pronominal, and sociopragmatic problems encountered in translating gender terms from English into Uzbek. English employs natural gender through pronouns (he/she/they), lexical pairs (actor/actress), and modern inclusive neutral forms (chairperson, singular they), which sharply contrast with Uzbek’s complete absence of grammatical gender. The invariant third-person pronoun u in Uzbek, along with its neutral occupational terms, creates significant challenges. The study examines lexical asymmetries and gaps in occupational and role terms, referential ambiguity caused by pronominal neutralization, and sociopragmatic clashes when rendering feminist, queer, and identity-sensitive terminology within Uzbekistan’s traditional hierarchical context. Drawing on examples from literary, media, legal, medical, and everyday texts, the dominant translation strategies—neutralization, explicitation (insertion of erkak/ayol), cultural substitution, borrowing, and restructuring—are evaluated in detail. Through comparative-analytical, corpus-based, and experimental methods, the findings reveal that Uzbek’s neutral grammar facilitates functional equivalence but often erases source-text gender specificity, requiring compensatory explicitness that affects tone, length, rhythm, and pragmatic force. The article offers context-aware, socioculturally sensitive recommendations for translators, educators, and policymakers, along with suggestions for future research.